Prevalence and Toxinotyping of Clostridium Perfringens Enterotoxins in Small Ruminants of Samsun Province, Northern Turkey - Tütüncü, M.; Kiliçoğlu, Y.; Güzel, M.; Pekmezci, D.; Gülhan, T. (Pakistan Agricultural Scientists Forum drmabdullah.uvas@yahoo.com, 2018)
Enterotoxemia, caused by Clostridium perfringens, is one of the most common problems of small ruminants’ industry worldwide. C. perfringens is considered to be a normal resident of the intestines and when the intestinal environment changed, proliferates in large numbers and produces enterotoxins. Vaccination against C. perfringens enterotoxins is of paramount importance for preventing enterotoxemia in small ruminants. Therefore, detection of local enterotoxin types produced by C. perfringens could help deciding the suitable vaccine program. The present study was aimed to determine the types of C. perfringens and their toxins prevalent in small ruminant of Samsun province, Northern Turkey. For this purpose, 221 intestinal samples from sheep and goats with sudden death and/or suspected from enterotoxemia were examined by ELISA for detection of C. perfringens enterotoxins. According to ELISA results, 45.2% of the samples (100/221) were positive for enterotoxemia caused by C. perfringens. Overall, 133 enterotoxins were detected in this 100 positive samples. When evaluating the individual enterotoxins; alfa (α), beta (β), and epsilon (ε) toxin were detected in 72.9%, 4.5%, and 22.6%, respectively. According to toxin types, 65 for C. perfringens type A (65.0%), 1 for type C (1.0%), 5 for type C (5.0%), and 29 for type D (29.0%) were determined. In conclusion, it was determined that enterotoxemia was high (45.2%), C. perfringens A and D type dominant strain in sheep and goats in Samsun province. A suitable vaccination program against C. perfringens type A and type D may provide adequate protection against the enterotoxemia of small ruminants in this area. © 2018, Pakistan Agricultural Scientists Forum. All rights reserved.
Keywords: Clostridium Perfringens; Enterotoxemia; Enterotoxin Types; Goat; Sheep